Eutrema EsMYB90 Gene Improves Growth and Antioxidant Capacity of Transgenic Wheat Under Salinity Stress - Li, Chuanshun; Zhao, Yaoyao; Qi, Yuting; Duan, Chonghao; Zhang, Hengyang; Zhang, Quan (Frontiers in Plant Science, 2022)
Ectopic expression of the EsMYB90 transcription factor gene from halophytic Eutrema salsugineum has been reported to enhance the level of anthocyanin and other flavonoid metabolites in transgenic tobacco. In this study, the wheat JW1 overexpressing EsMYB90 showed longer roots and higher fresh weight than that in wild type under salt stress. And the transgenic wheat plants displayed significantly higher peroxidase (POD) and glutathione S-transferase (GST) activity, as well as a markedly lower malondialdehyde (MDA) content than that of wild type during salt stress condition. Analysis of histochemical staining and H2O2 level indicated the accumulation of reactive oxygen species (ROS) was significantly lower in the roots of transgenic wheat plants compared to wild type under salt stress. Transcriptome analysis revealed that EsMYB90 gene affected expression of a considerable amounts of stress-related genes that involved in phenylpropanoid biosynthesis and antioxidant activity in transgenic plants subjected to NaCl treatment. Importantly, the significantly upregulated expression genes in transgenic wheat under salt stress were mainly associated in the antioxidative enzymes POD and GST encoding genes compared with wild type. Furthermore, EsMYB90 is suggested to bind with the MYB-binding elements of pTaANS2 and pTaDFR1 by dual luciferase assay, to activate transcription of TaANS2 and TaDFR1 genes that encoding key enzymes of anthocyanin biosynthesis in transgenic wheat plants. All the results indicated that, under salt stress, the EsMYB90 gene plays an crucial role in preventing wheat seedlings from oxidative stress damage via enhancing accumulation of non-enzymatic flavonoids and activities of antioxidative enzymes, which suggested that EsMYB90 is an ideal candidate gene for genetic engineering of crops.